2006
DOI: 10.1097/01.mlg.0000221967.67003.1d
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Anterior Ethmoidal Artery Ligation: A Cadaver Study

Abstract: Endoscopic AEA ligation may be possible in some patients. The AEA should be in a mesentery for an effective clip to be placed and be associated with a dehiscence of the AEC. If the lateral lamella is classified as Keros grade 2 or 3, it is likely the AEC will be found in a mesentery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 11 publications
3
58
0
4
Order By: Relevance
“…The difference in thickness between the two was significant (Cochran and Cox t test, p < 0.05). In addition, the AEC presented a partial dehiscence in 33.3% of the cases, compared with defect rates of 11.4%, 8 16%, 16 and 66.7% 5 reported in the literature. The data demonstrated that the inferior bone wall's protection to the artery is weak, and the artery is more accessible -when distant from the ethmoid roof.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The difference in thickness between the two was significant (Cochran and Cox t test, p < 0.05). In addition, the AEC presented a partial dehiscence in 33.3% of the cases, compared with defect rates of 11.4%, 8 16%, 16 and 66.7% 5 reported in the literature. The data demonstrated that the inferior bone wall's protection to the artery is weak, and the artery is more accessible -when distant from the ethmoid roof.…”
Section: Discussionmentioning
confidence: 82%
“…7,13,17 Floreani et al 16 measured the range of the posterolateral to anteromedial angle as 30 degrees to 45 degrees as it passed from the orbit to the anterior cranial fossa. Cankal et al 15 observed that AEC left the orbit at an angle of 12 to 50 degrees anteriorly, and the angle was superiorly 0 to 45 degrees and inferiorly 0 to 20 degrees on coronal images.…”
Section: Discussionmentioning
confidence: 99%
“…1,[3][4][5]8,9,[11][12][13][14]40,41 On the other hand, we found few papers describing studies using CT. 6,17,18,33,39 In assessing the anatomical landmarks for locating the anterior ethmoidal artery, we found that the medial notch of the orbit (anterior ethmoidal foramen) and the anterior ethmoidal sulcus on the lateral wall of the olfactory fossae were reliable parameters, since they were seen respectively in 100% and 98% of CT exams. Gotwald et al 17 assessed 40 coronal plane CT exams using similar technical settings as ours, and showed that the medial notch of the orbit and the anterior ethmoidal artery sulcus were found respectively in 95% and 84% of exams.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,12,39 Injury of the anterior ethmoidal artery during endoscopic procedures may occur, with severe consequences. Preoperative knowledge of the course of the artery is essential to avoid complications; this important task belongs to CT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation